Deaf students and South African Sign Language (SASL) in teacher training: Avoiding a Procrustean “BEd” - du Plessis, Colleen Lynne (Journal for Language Teaching, 2025)
South African Sign Language (SASL) is the main language of learning and teaching (LoLT) for Deaf students in South Africa. To provide education of a high standard to the Deaf, suitably qualified teachers are needed. However, teachers at schools for the Deaf are not currently required to have any specialised training or qualification in Deaf education; neither are they required to be fluent in SASL. This problematic situation is exacerbated by the fact that owing to misconceptions about SASL and a deficit view of its capabilities in academic contexts, generic curricula that rely on English as the LoLT continue to be used. There is a need to ensure that appropriate pedagogies are used with Deaf students and that they develop academic literacy in both SASL and English. This appraisal of institutional policies and plans and academic program structures at one institution responsible for the training of Deaf pre-service teachers is aimed at aligning policy and practice with the needs of Deaf students and promoting the further development of SASL as an academic language. It identifies a number of principles that can enhance the inclusivity and quality of education provided to Deaf students undergoing teacher training.